Wound dehiscence prevalence and relationship with prosthetic material extrusion in women underwent anterior colpotomy. (November 2021) - Balzarro, Matteo; Rubilotta, Emanuele; Mancini, Vito; Serati, Maurizio; Gubbiotti, Marilena; Braga, Andrea; Saleh, Omar; Torrazzina, Marco; Malanowska, Ewelina; Serni, Sergio; Carrieri, Giuseppe; Antonelli, Alessandro; et al.
Aim: To assess the prevalence of anterior vaginal wall dehiscence in women who underwent anterior vaginal wall colpotomy for pelvic organ prolapse or stress urinary incontinence and to evaluate the influence of suture materials and techniques on wound dehiscence. Materials and Methods: This multicenter, prospective study enrolled naïve women for urogynecological surgery affected by anterior vaginal wall defect or stress urinary incontinence. Performed surgical procedures were anterior vaginal wall repair (AVWR) with native tissue (N-AVWR) or polypropylene mesh (M-AVWR), trans-obturator polypropylene in-out middle urethral sling (MUS). Used suture materials were Vicryl 2-0, Vicryl Rapide 2-0, and Monocryl 3-0. Suture techniques were running interlocking or interrupted. Follow-up was performed daily during hospitalization and in outpatient clinic after 10–14, 30 days, and after 3 months. Results: A total of 1139 patients were enrolled. AVWR were 790: 89.1% N-AVWR, and 10.9% M-AVWR. Polypropylene MUS were 349. Women with prosthetic implantation were 38.2%, while 61.8% had native tissue repair. Overall Vicryl was used in 53.9%, Vicryl Rapide in 37.4%, and Monocryl in 8.7%. Overall running interlocking sutures were 66.5%, while interrupted were 33.5%. Overall wound dehiscence prevalence was 0.9% (10/1139). Wound dehiscence rate of 0.6% (5/790) was documented in AVWR: 0.3% (2/704) in N-AVWR, and 3.5% (3/86) in M-AVWR. Among women underwent MUS, 1.4% (5/349) showed wound dehiscence. In patients who underwent prosthetic surgery, the overall dehiscence prevalence was 1.8% (8/435). A statistically significant higher rate of wound dehiscence was found in women with implanted prosthetic materials. Discussion: We reported for the first time the prevalence of wound dehiscence in females who underwent colpotomy for AVWR or MUS. Wound dehiscence occurrence was low, but non-negligible. We found that this complication was poorly associated to the suture methods and materials, while prosthetic material represented a risk factor for wound healing.